2010
DOI: 10.3758/s13414-010-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Dimension intertrial and cueing effects in localization: support for pre-attentively weighted one-route models of saliency

Abstract: There are several alternative accounts of dimensional intertrial and cueing effects in singleton feature search tasks. Some accounts assume that these effects arise at post-selective processing stages; dual-route accounts assume them to be perceptual in nature, but coming into play only in non-spatial tasks (e.g., detection but not localization). By contrast, the Dimension Weighting Account (DWA) assumes dimensional effects to arise at pre-attentive processing stages of spatial as well as non-spatial tasks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 58 publications
6
31
0
Order By: Relevance
“…It assumes that the weighting of features and dimensions is hierarchically organized, such that the weighting of a particular feature will always involve an increased weighting of all features defined in the same dimension compared to features of other dimensions (see also Figure lb). This idea of top-down "hierarchical feature weighting" is supported by results of a trialby-trial symbolic precueing experiment (Müller, Reimann, & Krummenacher, 2003; see also Zehetleitner, Krummenacher, et al, 2011): The cueing benefits in this experiment were comparable regardless of whether the target was actually defined by the cued feature or rather by another feature in the same dimension; for example, when observers, in response to the cue word "red," prepared for a target defined by the color red (79% cue validity), a blue target (with a 7% likelihood) was detected almost as fast as the cued target, but faster than a target defined by left-or right-tilted orientation (each with a 7% likelihood). Similarly, Meeter and Theeuwes (2006) reported that cueing the target identity not only speeded up target detection, but also infiuenced distractor interference: distractors defined in the cued dimension (but by another feature) caused larger interference as distractors defined in another dimension (see also Schubö & Müller, 2009, for electrophysiological evidence of differential processing of intra-vs. cross-dimensional distractors).…”
Section: What Is the Specificity Of Top-down Control?mentioning
confidence: 81%
“…It assumes that the weighting of features and dimensions is hierarchically organized, such that the weighting of a particular feature will always involve an increased weighting of all features defined in the same dimension compared to features of other dimensions (see also Figure lb). This idea of top-down "hierarchical feature weighting" is supported by results of a trialby-trial symbolic precueing experiment (Müller, Reimann, & Krummenacher, 2003; see also Zehetleitner, Krummenacher, et al, 2011): The cueing benefits in this experiment were comparable regardless of whether the target was actually defined by the cued feature or rather by another feature in the same dimension; for example, when observers, in response to the cue word "red," prepared for a target defined by the color red (79% cue validity), a blue target (with a 7% likelihood) was detected almost as fast as the cued target, but faster than a target defined by left-or right-tilted orientation (each with a 7% likelihood). Similarly, Meeter and Theeuwes (2006) reported that cueing the target identity not only speeded up target detection, but also infiuenced distractor interference: distractors defined in the cued dimension (but by another feature) caused larger interference as distractors defined in another dimension (see also Schubö & Müller, 2009, for electrophysiological evidence of differential processing of intra-vs. cross-dimensional distractors).…”
Section: What Is the Specificity Of Top-down Control?mentioning
confidence: 81%
“…However, according to Maljkovic and Nakayama [47], priming effects for the orientation dimension, as an aftereffect of having been assigned the target role in the distractor experiment, should dissipate within a few trials in the baseline salience measurement. Third, stimulus salience might be different in the distractor experiment because of top-down weighting [48][51]. When both stimuli are presented together, as in the distractor experiment, the weight of the target might be up-modulated and that of the distractor down-modulated.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of Müller et al (2003; see also Zehetleitner et al, 2011) cuing study show that dimension-based processing modules can be modulated by semantic foreknowledge of the target item in a dynamic (trial-by-trial) fashion. A related question is whether a top-down attentional set affects dimension-based processing for an extended time range such as the duration of an experimental block or an entire experiment.…”
Section: Dimension Weightingmentioning
confidence: 89%